2016
DOI: 10.1007/s12035-016-0012-2
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Significantly Improves Chronic Stress-Induced Impairments of Cognition and Synaptic Plasticity in Mice

Abstract: The aim of this study was to examine if nicotine was able to improve cognition deficits in a mouse model of chronic mild stress. Twenty-four male C57BL/6 mice were divided into three groups: control, stress, and stress with nicotine treatment. The animal model was established by combining chronic unpredictable mild stress (CUMS) and isolated feeding. Mice were exposed to CUMS continued for 28 days, while nicotine (0.2 mg/kg) was also administrated for 28 days. Weight and sucrose consumption were measured durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 65 publications
1
23
0
3
Order By: Relevance
“…The majority of these are membrane proteins and many have roles in metabolism and are involved in intramembrane cleavage of integral membrane proteins, such as Notch receptors, as well as in APP processing. To this end, previous evidence supports the potential effect of nicotine on Notch signaling [61,62] and APP expression [39,40]. A smaller, yet interesting, cluster was composed of the proteins MSMO1, FDFT1, and CYP51A1.…”
Section: Gene Ontology and Interaction Analysis Classification Revealmentioning
confidence: 72%
“…The majority of these are membrane proteins and many have roles in metabolism and are involved in intramembrane cleavage of integral membrane proteins, such as Notch receptors, as well as in APP processing. To this end, previous evidence supports the potential effect of nicotine on Notch signaling [61,62] and APP expression [39,40]. A smaller, yet interesting, cluster was composed of the proteins MSMO1, FDFT1, and CYP51A1.…”
Section: Gene Ontology and Interaction Analysis Classification Revealmentioning
confidence: 72%
“…Mice were brought into the room where the behavioral tests were conducted 60 min prior to the test start. Mice were placed in the center of the open-field apparatus (rectangle polycarbonate, 42×28 cm) illuminated at approximately 200 lux and allowed to explore for 5 min ( Harro et al, 1999 ; Shang et al, 2017 ). The animals were tracked to determine the amount of time spent in the center area (28×14 cm).…”
Section: Methodsmentioning
confidence: 99%
“…NMDA receptor subunits (NR1, NR2A, and NR2B) and AMPA receptor subunits (GluA1 and GluA2) are closely involved in brain function, and are also important targets of chronic stress ( Costa-Nunes et al, 2014 ; Pacheco et al, 2017 ; Shang et al, 2017 ; Arcego et al, 2018 ). The effects of chronic stress on NMDA and AMPA receptors vary based on the type of stress.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Costa-Nunes et al (2014) found that social defeat and predation stress increased NR2A mRNA expression, but not the expression of NR2B and NR1 mRNA in the hippocampus of mice. In chronic unpredictable mild stress, the levels of NR2A and NR2B were significantly reduced ( Shang et al, 2017 ), the levels of GluA2 and GluA3 were significantly elevated while the level of GluA1 was not changed ( Lin et al, 2018 ). In the present study, we also evaluated the expression of NMDA receptor subunits (NR1, NR2A, and NR2B) and AMPA receptor subunits (GluA1 and GluA2).…”
Section: Discussionmentioning
confidence: 99%